THE ROLE AND IMPORTANCE OF BASKETBALL IN PHYSICAL EDUCATION CLASSES - B. Dj .Davrambekov (Galaxy International Interdisciplinary Research Journal, 2023)
basketball game is also a component of sports games. As a result, it has a proper place in the new national educational standards and its program of the Republic of Uzbekistan. Both small and big play this game equally curious around the world. The basketball game has entered our country from the 1920s. It is currently included in the program of all educational institutions. In fact, the game originated in the US more than 110 years ago. It was thought of by Springfield College physical education teacher James Naismith and played with his students. At that time, the ball wouldn’t be thrown into a ring like it is now, but thrown into a simple basket. "Basketball" is an English word meaning "basket," "basket," "bol," and "ball."